Intelligent music teaching : essays on the core principles of effective instruction - Duke, Robert A.; University of Texas at Austin. Center for Music Learning (Austin, Texas : Learning and Behavior Resources, 2015)
In this collection of essays, the author describes fundamental principles of human learning in the context of teaching music. Written in a conversational style, the individual essays outline the elements of intelligent, creative teaching. Duke effectively explains how teachers can meet the needs of individual students from a wide range of abilities by understanding more deeply how people learn. Teachers and interested parents alike will benefit from this informative book.
Precision in language and thought -- What to teach -- Assessment -- Sequencing instruction -- Feedback -- Transfer -- Effecting change -- A teaching life.
"Center for Music Learning, The University of Texas at Austin."
Keywords: Music -- Instruction and study